Three-dimensional discrete element simulation of electrode structural evolution in lithium-ion batteries during drying and calendering - Yuhang Lyu; Shaohai Dong; Li Ting Gao; Zhan-Sheng Guo (International Journal of Electrical Power & Energy Systems)
The drying and calendering processes are critical in the manufacture of electrodes for lithium-ion batteries, and have a profound effect on their mechanical and electrochemical properties. In this study, we developed a three-dimensional representative volume element (RVE) model of electrodes, which includes the active material, carbon binder domain, solvent, and particle contacts. Utilizing the discrete element method (DEM), we continuously simulated the structural evolution of the RVE during the drying and calendering processes. Our simulations revealed a three-stage drying scheme consistent with experimental observations, demonstrating the accuracy of our DEM-based approach. Furthermore, we found that the calendering process significantly enhances the mechanical integrity and electronic conductivity of the electrodes, with peak stresses occurring in the thickness direction. This research underscores the potential of DEM in elucidating electrode heterogeneity during manufacturing processes and highlights the innovative use of this method in the field of battery science.